AKTIVITAS ANTIKANKER EKSTRAK ETANOL TANAMAN TAPAK LIMAN (Elephantopus scaber L.) TERHADAP SEL T47D MELALUI INDUKSI APOPTOSIS - Panji Ratih Suci; Nurkhasanah Nurkhasanah; Nanik Sulistyani (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2021)
Breast cancer is the most dominant type of cancer in Indonesia. Traditional medicine using tapak liman (Elephantopus scaber L.) as an anticancer becomes an option because it contains compounds such as sesquiterpenes. The purpose of this study was to know the cytotoxic activity of ethanolic extract of tapak liman on T47D cells through induction of apoptosis. The extraction method uses maceration with 96%. Total flavonoids were tested using quercetin as a spectrophotometric standard. ethanol solvent, cytotoxic test using microtetrazoliom (MTT assay), and apoptosis test using double staining test (ethidium bromide-acrydine orange) under a fluorescence microscope. The results showed the linear regression equation y = 0.0934x-0.0292 with the resulting flavonoid levels of 0.979% w / w calculated against quercetin (QE) The concentration of the compound used was 1000 µg/ml; 500 µg/ml; 250µg/ml; 125 ?g/ml, 62.5 ?g/ml; 31.25 µg/ml. The MTT assay results are the values of IC50 which are analyzed using probit analysis and apoptosis tests which are analyzed descriptively. The results of the research show that the ethanol extract of tapak liman using MTT method has IC50 value of 59 µg/ml, while the testing of double staining method shows the color of bright green which indicates early apoptosis and the color orange in the cells which undergoing final apoptosis. DNA fragmentation results shows that Tapak Liman extract induces DNA fragments. The conclusion of this study is that tapak liman textract has the potential for cytotoxic activity against T47D breast cancer cells through the induction of apoptosis